Decent work in global food value chains: Evidence from Senegal - Fabry, Anna; Van den Broeck, Goedele; Maertens, Miet (2020)
The rapid growth and transformation of global food value chains has stimulated the development of rural labour markets, and has important consequences for rural poverty reduction. While there is consensus that this transformation is associated with substantial rural employment creation, there is still debate on the inclusiveness and quality of these jobs. We provide quantitative evidence on the quantity and inclusiveness of wage employment in the horticultural sector in Senegal, and on the quality of this employment and discrimination towards vulnerable groups of workers. We use survey data from 525 workers, 392 workers in agro-industrial companies and 133 workers on small-scale horticultural farms. We assess the inclusiveness of employment towards female, young and migrant workers, and compare the quality of employment between these groups of workers and between the agro-industrial and the small-scale farm sectors. The quality of employment is assessed through wages and a decent work index that captures multiple wage and non-wage dimensions of job quality. We use bivariate and multivariate analyses to examine quality of employment and a decomposition analysis to examine discrimination. Results suggest that the agro-industry is inclusive towards migrant, female and young workers, but that discrimination in job quality occurs within and across companies. Results illustrate substantial gender and youth wage gaps, and a lower likelihood of having decent employment among migrant and young workers. Our results suggest that discrimination, for all dimensions of job quality, is mainly indirect.